PENGARUH KARAKTERISTIK INDIVIDU DAN MOTIVASI KERJA TERHADAP PENERAPAN STANDAR AUDIT BERBASIS PRINSIP (INTERNATIONAL STANDARDS ON AUDITING) (Studi Eksperimen Pada Mahasiswa Akuntansi Universitas Sriwijaya) - Henny Pratiwi; Tertiarto Wahyudi; Arista Hakiki (AKUNTABILITAS, 2017)
The comprehension and application of the Principle Based Audit Standards (International Standards on Auditing) is must be done by auditors in Indonesia. However, each individual characteristic has a different way of understanding and applying that standard. This study aims to measure the influence of individual characteristics and motivation on applying Principle Based Audit Standards (ISA). This study used an experimental method with posttest only control design. Quantitative data was obtained in interval scale that states performances in applying the Principle Based Audit Standards (ISA). The experimental results show that there are interactions between individual characteristics and motivation. Individuals with non-systematic characteristic have higher performance. While individuals with systematic characteristic will have higher performance if given a motivation.